2017
DOI: 10.1177/1178638817741281
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance Testing and Anthropometric Comparisons Among Rural Residents of Kyiv Region: Investigating the Possible Effect of Childhood Starvation—A Community-Based Study

Abstract: A relationship between childhood starvation and type 2 diabetes mellitus (T2D) in adulthood was previously indicated. Ukraine suffered a series of artificial famines between 1921 and 1947. Famines of 1932 to 1933 and 1946 were most severe among them. Long-term health consequences of these famines remain insufficiently investigated. Type 2 diabetes mellitus screening was conducted between June 2013 and December 2014. A total of 198 rural residents of Kyiv region more than 44 years of age, not registered as pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In a similar manner, accelerated growth by premature infants fed formula diets are at a greater risk of developing MetS in early childhood than normal term infants fed breast milk [88,89]. By contrast, early childhood famine elicits the opposite effect, imprinting metabolism with a degree of protection against adult T2DM [90]. The link to changes in the microbiome based on response to the type of diet, especially hiCHO diet, that leads to early gut flora dysbiosis has been suggested [85,87,91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar manner, accelerated growth by premature infants fed formula diets are at a greater risk of developing MetS in early childhood than normal term infants fed breast milk [88,89]. By contrast, early childhood famine elicits the opposite effect, imprinting metabolism with a degree of protection against adult T2DM [90]. The link to changes in the microbiome based on response to the type of diet, especially hiCHO diet, that leads to early gut flora dysbiosis has been suggested [85,87,91].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion has important public health implications, now that proof of concept has been modelled by these experiments. One implication is that observational nutritional data in adults, even when enrolled as nondiabetic, can only weakly predict long term diabetes outcome attributed to diet unless or until the Cumulative GLoad can be better assessed, possibly for a number of years, and/or that the T2DM risk conferred by diet more appropriately reflects the diet-based induction of T2DM at an early age [85,86,87,90,91]. Our data on Nile rat variation related to genetic permissiveness appear similar to those in human populations, indicating that a large number of rats per diet ( n = 10–15) is required in such preclinical experiments to detect/illustrate these diet x gene interactions in this model.…”
Section: Discussionmentioning
confidence: 99%
“…However, five studies used individual self-reports of famine exposure. [26][27][28][29][30] Excess mortality was often used to approximate levels of famine severity in different locations. Due to the different nature of the exposures, study characteristics have been presented separately for famine studies (table 2) and documented severe malnutrition studies (table 3) along with the results of the risk-of-bias assessment.…”
Section: Study Population and Contextmentioning
confidence: 99%
“…17 18 21 41 51 Finally, one study of Ukrainian famine survivors reported reduced diabetes risk in childhoodexposed participants (OR 0.063; 95% CI 0.007 to 0.55) compared with unexposed controls. 26 Documented severe malnutrition studies The evidence indicates that severe childhood malnutrition is associated with impaired glucose metabolism in survivors, with 6/9 studies reporting a positive association with diabetes, reduced insulin sensitivity, or glucose intolerance. 15 16 23 42 52 53 Notably, a Jamaican study that differentiated between survivors of marasmus and kwashiorkor reported greater fasting insulin, increased glucose intolerance, and reduced insulin sensitivity in adult marasmus survivors only.…”
Section: Glucose Metabolism Outcomes Famine Studiesmentioning
confidence: 99%
“…Another one of our studies shows that individuals who starved during famines of 1932 to 1933 and/or 1946 in Ukraine had a decreased screening-detected diabetes mellitus prevalence several decades after the famine episodes. 66 Similar to the explanation of the dynamics of T2D incidence among Nauruan residents (rising and falling over the last 40 years) provided by Jared Diamond, 67 these data can be viewed as the result of natural selection in accordance with James Neel’s thrifty gene’ hypothesis. 68…”
Section: Discussionmentioning
confidence: 56%